Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.3109/15563659008993472
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicological evaluation of hospital sterilizer workers exposed to ethylene oxide

Abstract: Ethylene oxide is now frequently used to chemically sterilize heat-sensitive materials in the hospital setting. Previous reports of neurotoxic effects of ethylene oxide have been described in animals and humans. Recent reports suggest that cognitive deficits may be associated with chronic low-level ethylene oxide exposure. We undertook this study of hospital workers with chronic ethylene oxide exposure and compared them with a non-exposed control group in an attempt to detect neurological and neuropsychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The March issue of Journal of Toxicology Clinical Toxicology carries an editorial (1) and two research reports (2,3), all by investigators at University of California at San Francisco (UCSF), on the neurotoxicity of ethylene oxide (EtO). Attorneys for a company involved in EtO litigation have asked for a review of those and related materials.…”
Section: Leti'ers To the Editor Ethylene Oxide And Cns Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…The March issue of Journal of Toxicology Clinical Toxicology carries an editorial (1) and two research reports (2,3), all by investigators at University of California at San Francisco (UCSF), on the neurotoxicity of ethylene oxide (EtO). Attorneys for a company involved in EtO litigation have asked for a review of those and related materials.…”
Section: Leti'ers To the Editor Ethylene Oxide And Cns Dysfunctionmentioning
confidence: 99%
“…The editorial discusses problems of measuring the possible neurotoxicity of chemical substances, including EtO. The first research report, referred to herein as Estrin (1990), covers a study of hospital workers exposed to EtO and concludes that EtO "should be considered in a differential diagnosis of neuropsychological, peripheral and central nervous system dysfunction in workplace settings associated with ethylene oxide exposure. The second report, referred to here as Klees, covers a different group of hospital workers exposed to EtO and concludes that the findings "suggest that CNS dysfunction and cognitive impairment may result from chronic ethylene oxide exposure in hospital central supply units.…”
Section: Leti'ers To the Editor Ethylene Oxide And Cns Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies of the eVects of occupational factors on central nervous system (CNS) function using event-related potential (ERP) recording have been performed, in clinical cases of exposure to organic solvents (Morrow et al 1992;Chuwers et al 1995;Lindgren et al 1997;Verberk et al 2004) or hydrogen sulphide (Wasch et al 1989;Hirsch 2002), vibration syndrome (VS) (Hirata et al 1995), surveys on lead exposure Murata et al 1993;Hirata et al 2004), survey on manganese exposure (Wennberg et al 1991(Wennberg et al , 1992 survey on solvent exposure (Estrin et al 1990;Lundberg et al 1995;Vrca et al 1997;Morrow et al 1998), shift work (Yasukouchi et al 1995), vibroacoustic disorder (Martinho andCastelo 1999), and cervico-brachial disorders . Hirata et al (1995) reported that the P300 latencies of vibration syndrome (VS) patients were delayed compared with those of healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…While, acute exposures are known to cause nausea, bronchitis, pulmonary oedema; workers with chronic exposure are at risk of developing neurological disorders and cancer [11,12]. EtO is also a known alkylating (hydroxyethylating) agent, which can lead to the formation of adducts with DNA [13,14] and proteins like haemoglobin [15,16].…”
Section: Introductionmentioning
confidence: 99%